Acute Transfusion-Associated Lung Injury in Cardiosurgical Patients - N. A. Karpun; V. V. Moroz; A. N. Afonin; Yu. V. Khrenov; D. B. Fitilev (Общая реаниматология, 2008)
Objective: to study the prevalence of acute transfusion-associated lung injury (TRALI) amongst cardiosurgical intensive care unit (ICU) patients and to assess the contribution of this pathology to the total number of postoperative pulmonary complications and its influence on the course and outcome of the underlying disease. Subjects and methods. 515 patients who had been operated on for cardiovascular diseases at the N. N. Burdenko Main Military Hospital in 2005—2007 were retrospectively examined. A control group included 127 patients operated on without using donor blood preparations in the perioperative period. Results. Ten cases of evolving acute lung injury (ALI) etiologically associated with transfusion therapy were revealed. One case of TRALI was fatal, other cases required prolonged artificial ventilation (mean 36±2.5 hours), the length of their ICU stay increased by an average of 3.2±0.2 days as compared with that in the similar patients receiving no transfusion therapy. Conclusion. In 23% of cases, the development of ALI was etiologically associated with transfusion therapy. The incidence of TRALI was 2.3%; mortality was 10%. At the same time, the majority of the detected cases were not timely recognized as TRALI. The latter required assisted/artificial ventilation and increased length of ICU stay. Key words: acute transfusion-associated lung injury.